THE INFLUENCE OF GIBRAN GIAT EDUCATION GAME ON MATHEMATICS CONCEPTUAL UNDERSTANDING OF FOURTH GRADERS - Riswari, Lovika Ardana; Salamah, Ummi (JPSD (Jurnal Pendidikan Sekolah Dasar), 2023)
AbstractCurrently, many learners, while learning, tend to learn by memorizing, for example memorizing mathematics formulas. This matter made the fourth graders of Public Primary School 1 Jepang had mathematical misconceptions. Thus, they had a low mathematic conceptual understanding. This research determined the influence of the GIBRAN GIAT education game on the mathematic conceptual understanding of fourth graders at Primary School 1 Jepang. This quasi-experimental research applied one group pretest-posttest design. The sample consisted of all fourth graders at Primary School 1 Jepang, 20 students, 9 males, and 11 females. The researchers collected the data by observing, documenting, and testing. The researchers also applied expert judgment and requirement tests with the normality test of Kolmogorov-Smirnov assisted by SPSS Version 23. The researchers examined the hypotheses with a paired-sample t-test assisted by SPSS version 23. The results showed the differences in learners' mathematics conceptual understanding. The obtained paired-sample t-test results were sig < 0.05 or 0.000 lower than 0.05. Thus, the researchers concluded the implementation of the GIBRAN GIAT education game influenced the fourth graders' mathematics conceptual understanding at Primary School 1 Jepang, Mejobo District, Kudus Regency.Keywords: Educational Game, GIBRAN GIAT